2022
DOI: 10.32615/bp.2022.014
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the application of biosynthesis and metabolic engineering of flavonoids in plants

Abstract: Flavonoids are secondary metabolites widely distributed in plants. They not only confer a wide spectrum of pigmentation to plant flowers but also protect plants from various biotic and abiotic stresses. Simultaneously, these compounds also offer health benefits to humans. Significant efforts have been made to correlate specific flavonoid production with biosynthetic pathway gene expression. Some structure genes and transcription factors that regulate the biosynthetic pathway have been identified. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…It was speculated that the leaves and flowers had some medicinal properties, such as antidiabetic, anti-inflammatory, and anticancer [44]. In this experiment, it was observed that the methanol extract of the four parts showed varying degrees of yellow-green, indicating the significant presence of flavonoids, which can modify flowers' colors, enhance plant resistance, and provide nutritional value for human diets [45]. However, due to the complex structure of phenolic substances, the results of using this colorimetric method are not accurate enough.…”
Section: Total Phenolics Contentmentioning
confidence: 86%
“…It was speculated that the leaves and flowers had some medicinal properties, such as antidiabetic, anti-inflammatory, and anticancer [44]. In this experiment, it was observed that the methanol extract of the four parts showed varying degrees of yellow-green, indicating the significant presence of flavonoids, which can modify flowers' colors, enhance plant resistance, and provide nutritional value for human diets [45]. However, due to the complex structure of phenolic substances, the results of using this colorimetric method are not accurate enough.…”
Section: Total Phenolics Contentmentioning
confidence: 86%
“…In another line of research, the cloning of Solanum sogarandinum 7-O-glycomethyltransferase enzyme in transgenic flax plants significantly increased the accumulation and stability of flavonoid glycosides (anthocyanidins and flavonols), leading to a higher resistance to the fungus Fusarium and improved antioxidant and oil content of GM flax ( 379 ). Further information regarding scientific investigations on ME of plants PBPs can be obtained in the available literature reviews ( 366 , 367 ). Indeed, Microbial production of PPs using GM bacterial strains have also resulted in significant over-production of these health promising metabolites ( 360 , 380 ) which can be used to expand clinical and experimental studies on PPs.…”
Section: Using Modern Biotechnology For Me Of Pbpsmentioning
confidence: 99%